2021
DOI: 10.1101/2021.09.08.459464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 expresses a microRNA-like small RNA able to selectively repress host genes

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease (COVID-19), continues to be a pressing health concern. In this study, we investigated the impact of SARS-CoV-2 infection on host microRNA (miRNA) populations in three human lung-derived cell lines, as well as in nasopharyngeal swabs from SARS-CoV-2 infected individuals. We did not detect any major and consistent differences in host miRNA levels after SARS-CoV-2 infection. However, we unexpectedly discovered… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, the limited yield of non-PCR duplicate fragments, coupled with the low number of chimeric reads outside of the most abundant miRNAs, has hindered the widescale adoption of this powerful approach. With the ever-increasing catalog of miRNAs associated with human disease, coupled with the characterization of small RNAs produced by RNA viruses including SARS-CoV-2 that appear to utilize the host miRNA regulatory machinery (Pawlica et al, 2021), the ability to deeply profile targets for individual miRNAs of particular interest represents a novel opportunity to better understand the biological regulatory networks driven by individual microRNAs in a variety of context.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited yield of non-PCR duplicate fragments, coupled with the low number of chimeric reads outside of the most abundant miRNAs, has hindered the widescale adoption of this powerful approach. With the ever-increasing catalog of miRNAs associated with human disease, coupled with the characterization of small RNAs produced by RNA viruses including SARS-CoV-2 that appear to utilize the host miRNA regulatory machinery (Pawlica et al, 2021), the ability to deeply profile targets for individual miRNAs of particular interest represents a novel opportunity to better understand the biological regulatory networks driven by individual microRNAs in a variety of context.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of small RNA species from viral RNA genomes has been shown for multiple pathogens [Perez et al, 2010, Parameswaran et al, 2010 including coronaviruses [Morales et al, 2017]. However, previous studies investigating small RNA transcriptomes from SARS-CoV-1 and SARS-CoV-2 infected cells utilized ligationbased library preparation protocols for deep sequencing that captured predominantly 5'-Phosporylated/3'-OH RNA molecules such as microRNA [Pawlica et al, 2021;Singh et al, 2022;Zhao et al, 2022]. In contrast, one recent publication used a ligation-independent technique [Wyler et al, 2021] but limited analysis to the Argonaute-associated small RNAs including miRNA and vault RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have previously reported putative SARS-CoV-2-derived endogenous miRNAs [Pawlica et al, 2021;Singh et al, 2022;Zhao et al, 2022]. Specifically, using deep sequencing of small RNAs carrying 5'-phosphate and 3'-OH isolated from infected Calu-3, A549 and PC-9 cells, Pawlica and co-authors identified "CoV2-miR-O7a," encoded in the SARS-CoV-2 ORF7 [Pawlica et al, 2021]. These results were confirmed by Singh et al, who detected CoV2-miR-O7a.1 and its isoform CoV2-miR-O7a.2 in infected Caco-2 and A549-ACE2 cells [Singh et al, 2022].…”
Section: Read Counts Of Sars-cov-2 Viral Mirnas Versus Other Short Rnasmentioning
confidence: 99%
“…In fact, the Northern blot technique has allowed researchers to validate the occurrence of viral miRNA-like RNA structures in different viruses, including the H5N1 influenza virus (miR-HA-3p) and the Ebola virus (miR-VP-3p) ( Chen et al, 2016 ; Li et al, 2018 ). Intriguingly, a recent Northern blot assay-based study confirmed that the SARS-CoV-2 could encode the viral miRNA-like small RNA vmiR-5p from its ORF7a, which might be involved in the pathogenesis of the virus at issue ( Pawlica et al, 2021 ). Moreover, deep sequencing of infected Calu-3 and Vero E6 cells revealed that the nucleocapsid gene (N) of SARS-CoV-2, which critically regulates pro-inflammatory cytokines and lung pathology, may encode miRNAs, being the top three v-miRNA-N-28612, v-miRNA-N-29094, and v-miRNA-N-29443.…”
Section: The Molecular Crosstalk Of Viral-derived and Human Mirnas In Covid-19 Infection And Immune Responsementioning
confidence: 99%